(untitled) (Issues in Social and Environmental Accounting (ISEA), 2015)
To contribute to the debate concerning performance measurement, this study investigated some talent factors that can influence business performance of Indonesian finance industry and to provide a framework by which business leaders could assess their current management capa bilities. Using purposive sampling, 56 finance companies listed on Indonesia Stock Exchange in 2012 were selected. Corporate governance aspects were measured by employing 12 talent factors and business performance was measured using profit per employee, revenue per em ployee, and market capitalization per employee. 12 hypotheses were tested using multiple re gression analysis. The authors concluded on 2 things. Firstly, the greater the number of audit committee members, the higher the profit per employee and secondly, higher remuneration for directors and commissioners induced better business performance, as measured by three indi cators. However, larger number of employees worsens profit per employee, revenue per em ployee, and market capitalization per employee.